2003
DOI: 10.1007/s00113-003-0629-2
|View full text |Cite
|
Sign up to set email alerts
|

Wertigkeit der k�rperlichen und radiologischen Basisdiagnostik des Beckens in der Schockraumbehandlung

Abstract: The clinical diagnosis of pelvic instability should result in an immediate order for blood products, taking surgical intervention into account. Pelvic radiographs in the ER are required for early surgical management. In patients with negative pelvis examination results, a routine pelvic radiograph is recommended because clinical examination cannot reliably rule out surgically significant pelvic fractures (20%) in the severely injured and intubated blunt trauma patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(11 citation statements)
references
References 0 publications
1
8
0
2
Order By: Relevance
“…While it is easier to make the correct diagnosis in clinically alert patients, the examiner should be aware of missed injuries in unconscious and intubated patients. Here further diagnostic tools would be beneficial [26-28]. Some studies have revealed a lack of admission radiographs of the injured area as one reason for overlooked injuries and others have reported misinterpreted x-rays [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…While it is easier to make the correct diagnosis in clinically alert patients, the examiner should be aware of missed injuries in unconscious and intubated patients. Here further diagnostic tools would be beneficial [26-28]. Some studies have revealed a lack of admission radiographs of the injured area as one reason for overlooked injuries and others have reported misinterpreted x-rays [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, fractures of pelvis and long bones are commonly observed in middle aged people due to osteoporosis and falls and in young people usually due to severe hits [ 4 , 5 ]. Patients with severe pelvic fractures account for 3% of total fractures [ 6 ]. The complications of bone fracture include infection, avascular necrosis, large blood vessel damage, damage to the nerves, damage to the muscles, damage to the tendons, osteoarthritis and in certain cases, shock, fat embolism, compartment syndrome, lower extremity deep vein thrombosis (DVT) and lung embolism [ 7 - 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…A total of 2644 studies were screened. Twenty studies met the eligibility criteria and were included [10][11][12][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49] in the quality assessment and meta-analysis ( Fig. 1 and S- Table 1 in supplementary file).…”
Section: Resultsmentioning
confidence: 99%
“…The reference standards were x-ray [ 33 36 , 38 , 40 , 44 , 46 , 49 ], unclear [ 11 ], or x-ray or CT [ 10 , 12 , 37 , 39 , 41 43 , 45 , 47 , 48 ]. Findings were interpreted by a radiologist [ 33 35 , 39 , 41 , 43 , 45 , 46 , 49 ], surgeon [ 12 , 33 , 35 , 36 , 42 ], or an unreported specialist [ 10 , 11 , 37 , 38 , 40 , 44 , 47 , 48 ]. One study [ 48 ] focused on an unstable pelvic fracture.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation